2022
DOI: 10.4269/ajtmh.21-0686
|View full text |Cite
|
Sign up to set email alerts
|

School Sanitation-Related Psychosocial Stressors among Nigerian Students

Abstract: Psychosocial stressors are indicative of challenges associated with the social and environmental conditions an individual is subjected to. In a bid to clearly understand the present gaps in school sanitation, this cross-sectional study aimed to identify the sanitation-related psychosocial stressors experienced by students in a Nigerian peri-urban community and their associated impacts. A three-stage sampling technique was used to select 400 students from 10 schools. The students to toilet ratio were 1,521:0 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Similar trends of inadequate/ unavailable school WASH facilities in other geo-political zones have been reported by Ejimogu et al [32] in Owerri, South-East Nigeria; CODE [33] in Kaduna, Northwestern Nigeria; Yusuf et al [34], in Sokoto, Northwestern Nigeria; and Sanni et al [35] Gwagwalada, North Central Nigeria. Moreover, the trend of school WASH disparities between public and private schools in this study has also been reported by several other studies in Nigeria [16,21,35,36]. This is mainly because parents of private school students typically have higher educational status and income levels.…”
Section: Availability Of School Wash Facilitiessupporting
confidence: 85%
See 1 more Smart Citation
“…Similar trends of inadequate/ unavailable school WASH facilities in other geo-political zones have been reported by Ejimogu et al [32] in Owerri, South-East Nigeria; CODE [33] in Kaduna, Northwestern Nigeria; Yusuf et al [34], in Sokoto, Northwestern Nigeria; and Sanni et al [35] Gwagwalada, North Central Nigeria. Moreover, the trend of school WASH disparities between public and private schools in this study has also been reported by several other studies in Nigeria [16,21,35,36]. This is mainly because parents of private school students typically have higher educational status and income levels.…”
Section: Availability Of School Wash Facilitiessupporting
confidence: 85%
“…In addition, a recent survey has also suggested the possibility of school WASH inequalities and socio-economic disparities between government-owned (public) schools and private schools translating into MHM inequalities among in-school girls. The study revealed that girls attending public schools were 4.5 times more likely to be absent due to their inability to practice healthy MHM at school [21]. This string of social and economic inequalities potentially drives deeper, translating into other human rights issues like MHM inequalities, further impairing global efforts to achieve the Sustainable Development Goal 10 of significantly reducing inequalities by 2030.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have shown that school systems do not promote LUT health, and teachers and school nurses need improved education regarding LUTD and first‐line treatment options 7–22 . Ko et al surveyed elementary school teachers about their understanding of LUT health, activities that promote LUT health, and classroom rules around toileting.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have shown that school systems do not promote LUT health, and teachers and school nurses need improved education regarding LUTD and first-line treatment options. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Ko et al surveyed elementary school teachers about their understanding of LUT health, activities that promote LUT health, and classroom rules around toileting. The overwhelming majority of respondent teachers (82%) never had any professional development regarding bathroom regulations, had toileting rules that did not promote LUT health (76%), and encouraged students to hold their urine (88%).…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation